Forest Fevers: traditional treatment of malaria in the southern lowlands of Laos. (1st March 2020) - Elliott, Elizabeth; Chassagne, François; Aubouy, Agnès; Deharo, Eric; Souvanasy, Outhay; Sythamala, Phaiboun; Sydara, Kongmany; Lamxay, Vichith; Manithip, Chantanom; Torres, Juan Antonio; Bourdy, Geneviève
Abstract: Ethnopharmacological relevance: Malaria is still a highly challenging public health issue in southern Lao PDR, with increasing cases of artemisinin resistance and Plasmodium vivax infections which are more complicated to treat. Traditional medicine has a long history of use in Laos, and is primarily practised by traditional village healers, who possess unique bodies of transmitted knowledge focused on herbal prescriptions, including those for the treatment of malaria. Villagers also use plants for healthcare in the home. The aim of the study is to document local fever concepts and use of herbal remedies, and examine whether they may have potential as complementary treatments against malaria. Materials and methods: The study took place in Champasak province in the far south of Laos, in primarily lowland areas. First, 35 traditional healers across the 10 districts of the province were interviewed to elicit details about knowledge and treatment of fevers. Second, a household survey was conducted in a village in a malaria-endemic area; 97 households were interviewed on fever incidence, differentiation, treatment-seeking behaviour and knowledge of plant-based remedies for fevers. Plants indicated by both healers and villagers were collected and voucher specimens deposited in the herbarium of the National University of Laos for identification. Results: Malaria is a well-known pathology among the healers and villagers of lowland Champasak province; biomedical treatments are preferentially used, but traditional medicine is a popular complementary method, especially in chronic cases with additional symptoms. 30 different fever types were recorded, which were usually named symptomatically, and grouped into 12 categories. Some were described as forms of malaria, which was conceived as a dynamic, changing pathology affecting many body systems. Healers formulate treatments based on symptoms and the person's constitution, and with the intention of creating specific pharmacological actions associated with temperature or flavours. 11 of the healers gave prescriptions for malaria (27 in total), including 47 identified plant species. The most-used plants (4 or more use-reports) were also the most cited in the literature for use against malaria, demonstrating a correspondence between Lao healers and other traditional medical systems. Furthermore, some of these species show promising results for future research, especially Amorphophallus paeniifolius (Dennst.) Nicolson and Alocasia macrorrhizos (L.) G. Don. Conclusion: Traditional healers are important actors in the treatment of malaria in southern Laos, and herbal remedies should be evaluated further by the use of reverse treatment outcome trials, especially those which may be of use as complementary remedies in treating P. vivax. Initiatives on knowledge transmission, medicinal plant conservation and healthcare integration are also urgently needed. Graphical abstract: Image 1